PENGARUH PENYULUHAN KESEHATAN TERHADAP TINGKAT PENGETAHUAN MASYARAKAT TENTANG BAHAYA MEROKOK DI DESA SENTOSA KECAMATAN KRUENG SABE ACEH JAYA - Sopia, Nadia; Maysura, Futry (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2024)
According to WHO, every 6.5 seconds one person dies from smoking. Data from WHO shows that Indonesia has the highest number of smokers in the world after China and India. The number of smokers in the world according to WHO in 2009 reached 1.1 billion, consisting of 47% men, 12% women, and 49% children. Health can be achieved by changing unhealthy behavior into healthy behavior and creating a healthy environment in the household. Therefore, health needs to be safeguarded, maintained, and improved by every member of the household and championed by all parties. This research is a descriptive and survey research on household heads that presents the results of the description obtained in the field. This study aims to analyze the level of knowledge about the dangers of smoking and smoking risk factors in Sentosa Village, Krueng Sabe District, Aceh Jaya Regency. The results of this study showed that before being given counseling, 28.5% of respondents did not know the dangers of smoking and 71.4% of respondents knew the dangers of smoking. After counseling, the level of knowledge in filling out the questionnaire increased to 100% in the good category. These results indicate that there is an effect of counseling on community knowledge.